Hybrid electromagnetic Halbach array for wireless power transfer (WPT) system using variable and uniform pitch coils - Tamuno‐omie Gogo; Dibin Zhu (IET Power Electronics)
Abstract The electromagnetic Halbach array (EHA) for wireless power transfer (WPT), designed to improve the transferred power and power transfer distance, has been proven to be effective and can be applied in various consumer applications. This paper presents a hybrid form of the EHA, aimed at improving the quality of power generated and transmitted. The expression for the determination of the magnetic field of a variable pitch flat coil for wireless power transfer and other uses has been derived. The average magnetic field, magnetic flux, and power transfer efficiency are investigated. The power transfer efficiency and the average magnetic field generated by four different design considerations were compared. The hybrid electromagnetic Halbach array wireless power transfer system (HEHA‐WPTS) has also been studied and results are compared with the conventional arrangements. Simulations and experiments were carried out to verify the analytical results obtained. According to the results obtained, the HEHA‐WPTS, with a base coil with variable pitches and uniform side coils, produces a more uniform average magnetic field and a better average power transfer efficiency over a longer power transfer distance.